UNCOOPERATIVE CHILD REHABILITATION UNDER GENERAL ANAESTHESIA-CASE REPORT - Alexandrina Muntean; Andreea Simona Pop; Dana Gabriela Festila; Ada Gabriela Delean (Romanian Society of Oral Rehabilitation, 2021)
Aim of the study. Uncooperative children stand for a problem in paediatric dental practice, because dental rehabilitation cannot be achieved without difficulty. This paper emphasis on problems encountered in every day practice after children rehabilitation under general anaesthesia. Material and methods. 8 years old boy with cognitive and developmental problems with compromised dental status was treated under general anaesthesia in one day surgery. Results. Dental procedures performed under general anaesthesia must be follow by preventive regular appointment, with the purpose to increase patient compliance. For the first year after general anaesthesia, patient respect the preventive protocol but after that he abandons. Conclusions. General anaesthesia can help for uncooperative children dental rehabilitation, but active family involvement is necessary for accurate over time results.